Magnetobiology a historical view. - Valentinuzzi, M.E.
The objective of this article is to uncover as much as possible the origins and development of magnetobiology. The use of magnetobiology as a diagnostic tool and the technology associated with it such as biomedical MRI and magnetic source imaging are presented. Biomagnetism wherein excitable tissues are regarded as true generators of magnetic fields is also discussed.
Keywords: Biomagnetism; Biomedical MRI; Diagnostic tool; Excitable tissues; Historical view; Magnetic source imaging; Magnetobiology